Contribution to understanding the evolution of holometaboly: Transformation of internal head structures during the metamorphosis in the green lacewing Chrysopa pallens (Neuroptera: Chrysopidae) - Zhao, C (Springer Science and Business Media LLC, 2020)
10.1186/s12862-020-01643-2